Microbiological And Physicochemical Changes Of Green Coffee (Coffea Arabica) Fermentation In Kintamani, Bangli, Bali - Hatiningsih, Sayi; Semadi Antara, Nyoman; Wayan Gunam, Ida Bagus (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2019)
The excellent quality of the fermentation process is closely related to microbes involved in the process fermentation. This study aimed to compare the microbiological changes and physicochemical quality of green coffee during 16 hours fermentation. Lactic acid bacteria and yeast were the predominant microorganisms found throughout the fermentation process. The total lactic acid bacteria and yeast reached the highest value of 9.31 log10 CFU/g and 9.10 log10 CFU/g respectively on the coffee bean and 9.30 log10 CFU/g and 9.10 log10 CFU/g respectively on liquid of fermented coffee bean. The quantity of microflora on the coffee bean and liquid of fermented coffee bean increased and reached its maximum value after twelve hours and decreased after exceed its peak, while fungi was no detected during fermentation. Sixteen hours fermentation significantly (P<0.05) influenced the bulk density, moisture content and bean weight/100 beans, bean amount/10 g and cause defect to green coffee such us “broken beans”, “brown beans” and “partly black beans” yet were not significantly affected (P>0.05) bean size and color of the green coffee. Throughout coffee fermentation, the acids on the green coffee increased from 5.33 ± 0.144 to 9.99 ± 0.144% and the caffeine on the green coffee decreased from 3.70 ± 0.017 to 1.66 ± 0.003%. Phenol content on the green coffee and its brews also decreased successively from 1381.58 ± 8.40 to 980.16 ± 10.07 mg GAEs/100 g and 922.25 ± 17.961 to 812.06 ± 12.660 mg GAEs/100 g. While for the antioxidants capacity, green coffee was more stable and its brews increased successively from 11564.28 ± 255.345 to 112 34.428 ± 174.377 mg GAEAC/L and 32326.24 ± 22.744 to 38658.62 ± 180.107 mg GAEAC/L. It can be concluded that coffee fermentation had more a positive effect on microbiological changes and physicochemical quality of green coffee.